Analysis of Community-Based Tourism Destination Management System of Kometa Archery Condet - Rizki Nurul Nugraha; Arsya Tri Ananda; Auliah Nurlizah; Dena Fitria Januarty (Westscience Press, 2024)
Community participation is an indicator of success in community-based tourism. A tourism destination must include local communities to create mutually beneficial cooperation and synergy. Kometa Archery is one of the destinations in the Condet tourist village, because of its uniqueness, namely as an archery tourist attraction located on the edge of the river so the atmosphere is very cool and shady. Kometa Archery implements community participation, so that it has a positive impact on improving the economy of the surrounding community. This research aims to analyze the management system and community participation at Kometa Archery Condet. This research uses a descriptive qualitative approach method to get a complete picture of the Kometa Archery management system, so in this research the researcher uses primary data and secondary data obtained from field observations, interviews, documentation and literature studies. Then analyze the data results using the SWOC analysis method. The research results show that Kometa archery has a good management system and involves community participation in developing the destination.